Test of the Plant Density Reaction of Genotype Sunflower Hybrids - Szabó, András; Pepó, Péter (Acta Agraria Debreceniensis, 2005)
In order to produce sunflower in Hungary today it is important to develop hybrid-specific cropping technologies. The ever widening number of hybrids makes the constant examination of genotypes necessary from the viewpoint of genotype-environment interactions and critical elements. Plant density as a complex factor puts strain on the pathological features, yield and quality of sunflower. The experiment’s main objective is to find the optimal plant density for both the genotype and external factors. As a result it can be stated that the optimal crop density is between 45,000-75,000 plant/ha. In 2001 the optimal density was 55,000 plant/ha. The Aréna PR and the Alexandra PR hybrids produced the greatest yields (3511 kgha-1; 3338 kgha-1). In the growing season of 2002, the yields were higher than in the previous year and the optimal crop density was 45,000-65,000 plant/ha. The best yields were produced by the Aréna PR and Alexandra PR hybrids in this year again (4102 kgha-1; 4267 kgha-1) and in 2003, 45,000-65,000 plant/ha proved to be the best crop density. The highest yield was produced by the Alexandra PR. Analyzing the growing seasons of 2001, 2002 and 2003 it can be declared that as a result of dry climate of the three years yields were higher. It can be stated that the yield is decreased by higher than average of precipitation in the growing season.